1998
DOI: 10.1046/j.1365-2168.1998.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rebleeding and death from peptic ulcer in the very elderly

Abstract: Patients aged 80 years or greater had the highest risk of rebleeding and death. For patients below 80 years of age, significant factors related to a fatal outcome included co-morbid illness, complications and the need for mechanical ventilation. For patients aged 80 years or older, the significant factors were ulcer size greater than 2 cm and admission with serum bilirubin level above 20 mmol/l. Endoscopic treatment for the very elderly was effective if carried out early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 10 publications
6
41
0
1
Order By: Relevance
“…In a prospective study of 1,744 patients treated for peptic ulcer bleeding in China, patients over 80 years of age were found to have a significantly increased risk of rebleeding compared with patients younger than 80 years [50]. A second study in the USA found the age of 60 years or older to be associated with a significant increase in the risk of rebleeding (OR: 8.0; 95% CI: 2.8–22.8) [37].…”
Section: Resultsmentioning
confidence: 99%
“…In a prospective study of 1,744 patients treated for peptic ulcer bleeding in China, patients over 80 years of age were found to have a significantly increased risk of rebleeding compared with patients younger than 80 years [50]. A second study in the USA found the age of 60 years or older to be associated with a significant increase in the risk of rebleeding (OR: 8.0; 95% CI: 2.8–22.8) [37].…”
Section: Resultsmentioning
confidence: 99%
“…Except for the endoscopy itself, endoscopic treatment seems also to be an effective and generally safe treatment even when it is performed in the elderly [26,27] . In a previous study in elderly patients with peptic ulcer bleeding, no rebleeding or morbidity occurred when endoscopic treatment was performed early but there was a significantly greater risk of further bleeding and treatment related morbidity when treatment was performed after the onset of rebleeding [28] . On the other side, from the existing data, there is no evidence that peptic ulcer bleeding is more resistant to endoscopic therapy due to possible atherosclerosis of the underlying ar ter y.…”
Section: Discussionmentioning
confidence: 99%
“…The elderly are particularly susceptible to peptic ulcer disease (PUD) and complications due to their higher H. pylori prevalence and use of non-steroidal anti-inflammatory drugs (NSAIDs) (Bhala&Newton, 2005;Chow et al, 1998;Jones&Hawkey, 2001). Even if it is well known that the incidence of gastric ulcers increases in elderly people, little is known about gastric mucosal healing alterations during ageing.…”
Section: H Pylori Infection and Peptic Ulcer Diseasementioning
confidence: 99%